Effectiveness and Challenges of Cybercrime Law Enforcement in Bone Regency - Jumra, Jumra; Sandra, Gustika (Mahesa Research Center, 2025)
This study analyzes the effectiveness of cybercrime law enforcement in Bone Regency, South Sulawesi, as a representation of non-metropolitan areas adapting to digital transformation. A qualitative case study design was employed, involving in-depth interviews with 15 key informants, limited participatory observations, and document reviews of legal and policy frameworks. The findings reveal that current regulations remain insufficiently adaptive to emerging digital crime modes such as deepfakes, AI-driven fraud, and data theft via encrypted applications. Moreover, inter-agency coordination remains suboptimal, characterized by delayed cross-jurisdictional communication, the absence of standardized operating procedures (SOPs), and the limited capacity of local cyber units. From a technical standpoint, law enforcement agencies face challenges including a shortage of digital forensic experts, inadequate budgets, and insufficient network infrastructure. On the community side, low digital literacy persists, reflected in delayed case reporting, misconceptions about third-party responsibility mechanisms, and weak awareness of personal data protection. Nevertheless, the study also identifies adaptive initiatives, including collaboration with local communities, stakeholder engagement, and the mobilization of available resources. These findings underscore the urgency of regularly updating regulations, strengthening technical capacity, and promoting inclusive digital literacy programs. Such measures are essential for reinforcing cyber law systems and ensuring resilience against digital crime in non-metropolitan regions.